Tree species distribution along the environmental gradients in Pananjung Pangandaran Nature Reserve, West Java - AGUNG KURNIAWAN; PARIKESIT PARIKESIT (Biodiversitas Journal of Biological Diversity, 2008)
The research of tree species distribution along the environmental gradients in Lowland Tropical Rainforest Pananjung Pangandaran Nature Reserve had been conducted. The study aimed to elucidate the relationship between tree species distribution with â‰¥10 cm dbh and some measured environmental gradients, namely soil pH and moisture, soil depth, litter thickness, light intensity, altitude, slope, and the distance of plot from coastal line. A number of 125 of 10x10 m2 quadrats were established randomly in four transects. The results indicated that Rhodamnia cinerea was the species having the highest presence. Ordination technique using Canonical Correspondence Analysis (CCA) suggested that tree species were less evenly distributed along the measured environmental factors with Eigenvalue 0,387. Altitude was themost important environmental factor affected tree species distribution, soil moisture as well as light intensity.Key words: canonical correspondence analysis, distribution, lowland tropical rainforest, Pananjung Pangandaran